Managing multi-generation employees at work: understanding inter-generational employee differences with big-five models and their effects on job stress - Diaz Haryokusumo; Bambang Setia Wibowo (Diponegoro International Journal of Business, 2019)
This study aims to determine differences of employee’s personality between generation X and generation Y. We use the big five personality model consists of extraversion, agreableness, conscientiousness, neoriticsm, and openness to experience. This research also intended to examine the effect of big five personality on job stress on generation X and Y. The hypothesis was tested using independent sample t-test and multiple regression. The results of hypothesis testing on 126 samples indicated that there are no personality differences in the big five dimension among generation X and Y. The multiple regression results also do not show the influence of personality types on the level of work stress felt by generation X and Y. Additional analysis results show there is no difference in job stress level felt by generation X and Y.